EFEKTIVITAS AROMATERAPI UNTUK MENGURANGI MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER PERTAMA DI PMB AAN DYAH - Novitasari, Rista; Nufus, Hidayatun; Rosita, Evi (STIKES Borneo Cendekia Medika, 2024)
Nausea and vomiting are common complaints experienced by pregnant women in the first trimester, which can affect their quality of life and health. This study aims to evaluate the effectiveness of aromatherapy in reducing nausea and vomiting in first-trimester pregnant women. The research method used is a quasi-experimental design with a pretest-posttest design. The study sample consisted of 60 first-trimester pregnant women divided into two groups: the intervention group, which received aromatherapy treatment, and the control group, which did not receive the treatment. Aromatherapy involved the use of ginger and peppermint essential oils, applied through inhalation for 15 minutes, three times a day for two weeks. Data were collected using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) questionnaire before and after the intervention. The results showed a significant reduction in PUQE scores in the intervention group compared to the control group (p<0.05). These findings indicate that aromatherapy is effective in reducing nausea and vomiting in first-trimester pregnant women. This study suggests that aromatherapy can be considered a safe and effective non-pharmacological alternative for managing nausea and vomiting during pregnancy.